Peran Pemanfaatan Teknologi Informasi dan Komunikasi pada Sektor Ekonomi Kreatif di Indonesia - Angelia, Febri; Gultom, Yohanna (Jurnal Kebijakan Ekonomi, 2020)
This research aims at analyzing to what extent the role of information and communication technology (ICT) could support the performance of the creative economy sector that is rapidly growing in Indonesia. ICT in creative economy is not only helpful in promoting cost reduction or revenue generation as in business as usual, but also in itself is important asset to intensify the creativity of human resources which is the main production factor in creative economy. Using Ordinary Least Square (OLS) analysis method, this study analyzed cross section data from the Special Survey of the Creative Economy (Survei Khusus Ekonomi Kreatif/SKEK) by Indonesian Bureau of Statistics (Badan Pusat Statistik/BPS) in 2016 and found that although the use of ICTs delivers a positive effect on creative economy performance in general, the correlation varies depending on the type of activities or subsector of the creative economy in particular. The negative impact of the use of ICTs on firm performance is found in the visual communication design, music, application and games, and fine art subsectors. Furthermore, this study also uncovered that the use of ICTs in micro scale businesses was associated negatively with its performance. The result indicates that the type of subsectors and the scale of the firms are the determinants of whether ICT would have a positive effect in the performance of the creative economy.